Experimental study of properties for sand bricks with palm oil clinker as partial replacement for fine aggregate with ratio of 5% with rice husk 10%, 20% and 30% - Mohamad Safwan, Pauzi (2018)
Brick are widely used in construction and building material around the world. This research is to determine compressive strength, flexural strength, density and water absorption waste material such as palm oil clinker with rice husk as a replacement of fine aggregate (sand) for making a sand brick. From that waste material can be used to produce eco- friendly brick will give many benefit to all of us for example can reduce cost, can reduce from disposal to the land and idle. The ratio that used for replace fine aggregate which is sand are 5% palm oil clinker with 10%, 20% and 30% of rice husk. The ratio of the mortar is 1:6 which is consist of one (1) part of cement to six (6) parts of sand according to Jabatan Kerja Raya (JKR) of Standard Specification at section E (brickworks) in clause 3.1. The size of the sand brick according to the JKR specification is 225 mm x 113 mm x 75mm for one brick. In this process of curing there are two type of curing process that used for this experiment which is air curing and water curing. The sample the result on four testing which is compressive strength, flexural strength, density and water absorption. The testing procedure as per ASTM and JKR standard. The purpose of this research is to find the best ratio for making a good quality of sand brick based on JKR standard. The sample curing ages for this experiment are 3 days, 7 days, 14 days and 28 days. Each of curing ages days used 64 sand brick samples for the every testing but only the sample at curing age for 28 days used for testing density and water absorption. The highest compressive strength for the ratio that replace fine aggregate which is sand is air curing 5% clinker and 10% rice husk which is 8.02 MPa, the highest flexural strength for the ratio that replace fine aggregate which is sand is water curing 5% clinker and 10% rice husk which is 0.265 MPa, the highest density for the ratio that replace fine aggregate which is sand is air curing 5% clinker and 10% rice husk which is 17.95 kN/m3 and the lowest water absorption for the ratio that replace fine aggregate which is sand is air curing 5% clinker and 10% rice husk which is 4.65%. So, the conclusion is 5% clinker with 10% rice husk was the best ratio of this sand brick that replace fine aggregate (sand) with clinker and rice husk. The total of sample for this experiment including a control sample is 256 units.